2015
DOI: 10.5530/pj.2016.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Fruits of Gynochthodes umbellata (L.) Razafim. & B. Bremer–An Underutilized Edible Fruit Plant

Abstract: Objective: The present investigation aimed to assess the nutritional, mineral profiling and anti-nutritional analysis of Gynochthodes umbellata (Syn. Morinda umbellata), an underutilized edible plant belongs to the family Rubiaceae. Literature perusal reveals that, there are no previous reports on nutritional studies for this valuable fruit. Methods: Nutritional, mineral profiling and anti-nutritional analysis of fruits were carried out. Results: In nutritional analysis, carbohydrates (6.98 g/100g fw), protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
0
0
Order By: Relevance
“…21,22 The reason for increased anxiety scores during the cavity preparation and restoration visit maybe due to the sound and sight of the airotor hand piece; a possibility taken into account by Kleinknecht et al 23 Anxiety levels also increased during the stressful extraction visit because patient feel more anxious about tooth removal mainly due to the sight of needles than perceiving a pain or feeling helpless. 1,24 Similar results was also observed by Baldwin et al 25 This result was true in relation to pulse rate; However, no statistically significant difference was seen in relation to oxygen saturation, Clinical signs of anxiety include an increase in the heart rate and hyperventilation. 13 In the present study, no patients with hyperventilation were observed and this can be attributed to the no change in oxygen saturation of the patients before and after procedure.…”
Section: Discussionsupporting
confidence: 76%
“…21,22 The reason for increased anxiety scores during the cavity preparation and restoration visit maybe due to the sound and sight of the airotor hand piece; a possibility taken into account by Kleinknecht et al 23 Anxiety levels also increased during the stressful extraction visit because patient feel more anxious about tooth removal mainly due to the sight of needles than perceiving a pain or feeling helpless. 1,24 Similar results was also observed by Baldwin et al 25 This result was true in relation to pulse rate; However, no statistically significant difference was seen in relation to oxygen saturation, Clinical signs of anxiety include an increase in the heart rate and hyperventilation. 13 In the present study, no patients with hyperventilation were observed and this can be attributed to the no change in oxygen saturation of the patients before and after procedure.…”
Section: Discussionsupporting
confidence: 76%
“…The moisture content of C. oliviforme fruit was 61.30±1.60 % higher when compared to other fruits such as Grewia tenax (13.00 %) and G. flavescens (15%) reported by Elhassan and Yagi (2010). However, the moisture content of the fresh fruit was low when compared with other Chrysophyllum species described in the earlier work of Okwu et al (2018) and it was higher than the fruit of Gynochthodes umbellata (Sudhakaran and Nair, 2016). Besides, the relatively high moisture content observed in the sweet pulp indicated its short shelf life reported by Edem et al (2009) and Akpabio et al (2012).…”
Section: Chemical Properties Nutritional Analysismentioning
confidence: 66%